Skladnja v frazeologiji med sistemom in rabo - Kržišnik, Erika (Jezik in slovstvo, 2018)
Slovenian phraseology is relatively well researched from the lexicological perspective, but has been studied much less in terms of syntax. The topic of the present contribution is syntactic transformations ranging from transformations of the accusative into the genitive in negative sentences and the introduction of relative constructions to instances of passivisation and nominalisation. The topic is not new to Slovenian linguistics, having been first treated from the point of view of a native speaker/linguist in Kržišnik 1994. This was followed by a consensual survey of native speakers in which the transformations and their realisations were verified in the Fida corpus by Kržišnik (2005); subsequently, their usage was verified in the FidaPLUS corpus by Gantar (2007). For the purposes of the present contribution, a comparison was made with the usage in the Gigafida corpus. The latter mainly comprises journalistic texts, but 16% of its content is online texts. Thus, in addition to the overlap between native-speaker intuition and the use of idioms related to corpus type (size, temporal dimension, etc.), it is possible to observe the relationship between the use of idioms as determined by functional variation and their syntactic transformations.
Keywords: frazeologija; pooziraljenje; posamostaljenje; potrpnjenje; skladenjske pretvorbe; slovenščina